Membentuk Sikap dan Karakter Positif Remaja Melalui Edukasi Pencegahan Pergaulan Negatif dan Selalu Menjadi Remaja Positif SMK Fajar Ciseeng, Jl. Fajar, RT.007/RW003, Kelurahan Babakan, Kecamatan. Ciseeng, Kabupaten Bogor, Jawa Barat 16120 - Bayu Prasetyo; Ilham Gustiana Winata; Muhamad Andriyansyah; Irfan Rizka Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Adolescence is a period of development that is vulnerable to various environmental influences, including negative influences that can affect the formation of attitudes and character. The increase in deviant behavior among adolescents, such as inappropriate use of social media, promiscuity, and declining moral values, indicates the need for preventive efforts through ongoing education. This study aims to analyze the role of education to prevent negative social interactions in shaping positive attitudes and character in adolescents, as well as encouraging them to remain well-behaved individuals. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation of adolescent groups in educational settings and the community. The results show that education that focuses on strengthening moral values, ethics, responsibility, and character development can increase adolescent awareness of the consequences of negative social interactions. In addition, providing positive behavioral examples, consistent guidance, and the active role of parents, educators, and the social environment are very influential in shaping adolescents' attitudes to be more disciplined, confident, and future-oriented. Education to prevent negative social interactions also helps adolescents develop self-control and make wise decisions. Thus, the development of positive attitudes and character in adolescents depends not only on themselves but also requires good cooperation between family, school, and community. This research is expected to serve as a reference in developing effective character education programs, in order to create a generation of positive, well-mannered adolescents who are capable of facing social challenges in the modern era..